Ответ(ы) на вопрос:
У меня вот так получается только! Может, кто знает легче путь))
[latex] \frac{x^2+x-5}{x}- \frac{3x}{x^2+x-5}+4=0 [/latex]
[latex] \frac{(x^2+x-5)^2+3x^2+4x(x^2+x-5)}{x(x^2+x-5)} =0[/latex]
[latex]x^4+2x^3-9x^2-10x+25+3x^2+4x^3+4x^2-20x=0[/latex]
[latex]x^4+6x^3-2x^2-30x+25=0[/latex]
[latex](x^2+4x-5)(x^2+2x-5)=0[/latex]
*******************************************
[latex]x^2+4x-5=0[/latex]
[latex]D=4^2-4*1*(-5)=16+20=36; \sqrt{D}=6 [/latex]
[latex]x_{1/2}= \frac{-4\pm6}{2} =-5; 1[/latex]
***************************************************
[latex]x^2+2x-5=0[/latex]
[latex]D=2^2-4*1*(-5)=4+20=24; \sqrt{D}= 2 \sqrt{6} [/latex]
[latex]x_{1/2}= \frac{-2\pm2 \sqrt{6} }{2}= \frac{2(-1\pm \sqrt{6}) }{2}=-1\pm \sqrt{6} [/latex]
[latex]Answer:[/latex] [latex]-5; 1; \sqrt{6}-1; - \sqrt{6}-1 [/latex]
Не нашли ответ?
Похожие вопросы